MOODLE BASED E-LEARNING RESOURCE FOR REVISING CLINICAL ANATOMY: AN INEXPENSIVE AND INTERACTIVE SUPPLEMENT FOR PHYSIOTHERAPY STUDENTS (International Journal of Physiotherapy, 2016)
Background: Basic sciences like gross anatomy and physiology are the building blocks for all clinical courses. In the traditional physiotherapy curriculum, these basic medical subjects are covered in the first year of university course, whereas the clinical papers are pushed towards the final years, in conjunction with clinical practice. The time gap between these modules needs to be minimized to apply the basic science knowledge and achieve a strong understanding of the clinical conditions and treatment procedures. To bridge this gap, we tried to reintroduce these basic science concepts, including anatomy, imaging and biomechanics during the clinical modules.Methods: An online pack of ‘pre-clinical revision tasks’ was created using the students’ learning management system-Moodle for the 3rd semester physical therapy students in Universiti Kuala Lumpur - Royal College of Medicine, Perak. The students were asked to undertake a self-directed, learning and evaluation task before each clinical module. The online resource usage was monitored periodically within Moodle. A focus group interview was conducted and a 5 point Likert scale questionnaire feedback was obtained.Results: 83 students from the third semester participated in the study. Overall, 87% of the students utilized the resource,mainly after regular class hours. The students felt that the resource was useful (79%), made the clinical concepts simple (72%) compared to previous semesters.Conclusion: Such online resources tailor-made for each course and well integrated to the curriculum would definitely allow the students refresh their basic sciences knowledge essential for clinical practice.